Simulation Design Of A Baggage Handling System Based On Arduino Uno At The Airport Departure Terminal Dr. Ferdinand Lumban Tobing Sibolga - Ahmad Fahrur Rozi Matondang; Adi Sastra P Tarigan; M. Rizki Syahputra (Sean Institute, 2024)
Baggage handling plays an important role in ensuring the comfort of passengers traveling by airplane and ensuring that the baggage can be transported with the passenger on the same aircraft. However, passengers often do not know how to handle the luggage they have handed over at the check-in counter until it finally arrives in the plane's hold. This system is very important to support flight security and safety at an airport. The implementation of an automated baggage handling system (BHS) / Hold Baggage Screening (HBS) is very necessary to minimize cases of baggage theft. where this research aims to determine the Baggage Handling System (BHS) design planning at Dr. Ferdinand Lumban Tobing Sibolga, which is planned to use the Aerotropolis Airport concept. Apart from that, this research also aims to understand how the BHS components workDr. Airport Ferdinand Lumban Tobing SibolgaWhat is Planned.Where this research was carried out using the AutoCAD 2012 application and other engineering applications that allow easier planning and design. The BHS design used in this research refers to the BHS framework that has been implemented at Kuala Namu International Airport in Deli Serdang. The research results show that the BHS design has seven main stages, starting from check-in inspection, Out of Gauge (OOG) inspection to baggage that has a weight and dimensions that exceed the maximum size, X-Ray inspection MVXR 5000 (Screening Level 1/2), Manual Coding Station (MCS), X-Ray inspection RTT 110 (Screening Level 3/4), inspection by Avsec experts and reconciliation (Level 5/6), to the use of SCADA (Supervisor Control Data Acquisition).